Description of five new species of the Macrolycus venustus species group (Coleoptera: Lycidae) - R. L. Du; Y. X. Yang; X. K. Yang; H. Y. Liu (The European Zoological Journal)
Five new lycid species of the Macrolycus venustus species group have been discovered from China: M. acutus sp. nov., M. ramus sp. nov., M. microculus sp. nov., M. chonganensis sp. nov. and M. communis sp. nov. They are illustrated with habitus and male genitalia. Also, the aedeagus of M. sichuanensis Li etal. 2015 is illustrated and described to make comparisons with the new species. Additionally, a distribution map and an identification key to all species of the M. venustus species group are provided.